2014
DOI: 10.1249/01.mss.0000495712.08913.cf
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Caffeine On Repeated Upper/lower Body Wingates And Handgrip Performance

Abstract: International Journal of Exercise Science 8(3): 243-255, 2015.Caffeine enhances aerobic performance, but research is equivocal regarding anaerobic performance. This study examined effects of caffeine (7 mg/kg) on anaerobic performance in anaerobically active males (n = 10). Participants completed counterbalanced, double blind caffeine (Caf) and placebo (Pl) trials including a) 6 x 15 s upper body Wingates (UWant), b) 6 x 15 s lower body Wingates (LWant) and c) 6 x15 s maximal effort static hand grip test (HG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…One study examined the effects of caffeine on upper and lower body WANT performance using a repeated effort protocol (6 x 15 seconds). In the study by Andre, Green, Gann, O'Neal, and Coates (2015) a caffeine dose of 7 mg*kg -1 ingested one hour before the testing commenced, was effective for acute increases in peak and mean power output in the upper but not lower body. However, in this study, the participants completed both the upper and lower body WANTs in the same sessions (with the upper body test always preceding the lower body WANT) while in our study, the performance in these tests was examined on different testing days.…”
Section: Discussionmentioning
confidence: 99%
“…One study examined the effects of caffeine on upper and lower body WANT performance using a repeated effort protocol (6 x 15 seconds). In the study by Andre, Green, Gann, O'Neal, and Coates (2015) a caffeine dose of 7 mg*kg -1 ingested one hour before the testing commenced, was effective for acute increases in peak and mean power output in the upper but not lower body. However, in this study, the participants completed both the upper and lower body WANTs in the same sessions (with the upper body test always preceding the lower body WANT) while in our study, the performance in these tests was examined on different testing days.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers reported that an absolute dose of caffeine (250 mg) increased anaerobic cycling performance during a 6-s test using a force-velocity form of cycle ergometry [2]. In addition, researchers [1] have reported that peak power and mean power were significantly increased following ingestion of 7 mg/kg during repeated upper body Wingate tests, but that there were no significant effects of caffeine observed in lower body Wingate tests. Furthermore, Duncan et al [23] recently reported positive effects of caffeine on upper body WAnT compared to a dextrose placebo.…”
Section: Discussionmentioning
confidence: 99%
“…6 Bu sonuçlara benzer olarak akut kafein tüketiminin 1 tekrar maksimum kuvvette, tükenene kadar tekrar sayısında, 1 km bisiklet performansı sırasındaki anaerobik güç çıktısında, üst beden anaerobik, tekrarlı anaerobik performansında, 200 m koşu performansında, yüksek açısal hızlarda maksimum izokinetik diz ekstansör kuvvetinde, aktif ve skuat sıçrama yüksekliğinde artış etkileri raporlayan araştırma sonuçları bulunmaktadır. 14,[25][26][27]42,47,[49][50][51] Kafeinin ragbi, basketbol, bisiklet ve güreş gibi bazı takım sporlarında ve bireysel sporlarda anaerobik performansa pozitif etkilerinin olduğu araştırma sonuçlarıyla ortaya konulmuştur. Kafeinin anaerobik performansa pozitif etkilerinin olduğunu gösteren bu sonuçların aksine voleybol ve futbolcularda anaerobik performansa etkisi olma-dığını belirten araştırma sonuçları da bulunmaktadır.…”
Section: Discussionunclassified
“…23 Bununla beraber iyi antrenmanlı ya da rekreasyonel olarak aktif bireylerde dayanıklılık performansına ve anaerobik performansa pozitif etkileri olduğunu belirten sonuçlar bulunmaktadır. 24,25 Bunun yanı sıra sıçrama, sprint gibi kuvvet ve güç içeren kısa süreli ve yüksek şiddetli performansları artırdığını, değiştirmediğini ya da düşürdüğünü gösteren sonuçların olması bu konuda ortak bir konsensüs oluşmasını güçleştirmektedir. 2,21,[26][27][28][29][30] Bununla beraber kafeinin anaerobik aktivitelere etkileriyle ilgili yapılan çalışmaların çoğunluğu erkekler üzerinde yapılmış olup, kadın sporcularda çok sınırlı kaynak bulunmaktadır.…”
unclassified